An Audit of Intensive Care Services in Bangladesh (Ibrahim Medical College Journal, 2010)
This study was conducted to survey the facilities, bed strength, functional characteristics, manpower,operational practices and distribution of intensive care units in Bangladesh. Direct interview ofconsultants in charge of different Intensive Care Units (ICUs) in the city of Dhaka was conducted bya structured questionnaire. All Adult Intensive Care Units (ICUs) and Coronary Care Units (CCUs)with ventilator support in the city of Dhaka belonging to government and private sectors wereincluded. Our survey showed that 90% of all Intensive Care Units in Bangladesh were located in thecity of Dhaka. There were 40 Intensive Care Units in the city of Dhaka, of which 33 were ICUs and7 CCUs with ventilator support (also considered as ICU). Only 4 (10%) ICUs were located ingovernment hospitals. Rest of the ICUs was in private hospitals / clinics. Total number of ICU bedswas 424 and total numbers of beds in these hospitals were 8824. So 4.8% of total hospital beds wereprovisioned for critical care. Among these only 240 beds (60%) had ventilator support. 27(68%) ofthe 40 ICUs were multidisciplinary, 7(18%) CCUs, 5(12%) cardiac surgery and 1(2%) neurology.64% ICUs were run by anesthesiologists. 85% facilities were open units as opposed to 15% closedunits. Nurse: bed ratio of 1:1 was seen in 15(42%) facilities. On duty doctor: patient ratio wasvariable and highest was 1:4 in 9 ICUs (27 %). ICUs in Bangladesh are mainly situated in the cityof Dhaka and mostly in the private sector. The standards and management strategies vary greatly.Ibrahim Med. Coll. J. 2010; 4(1): 13-16Key words: Intensive Care Unit; Bangladesh; audit.DOI: 10.3329/imcj.v4i1.5929